Flare-up reaction of streptococcal cell wall induced arthritis in Lewis and F344 rats: the role of T lymphocytes. - van den Broek, M F (1990)
One i.p. injection of a sterile suspension of streptococcal cell walls (SCW) induces chronic erosive polyarthritis in susceptible Lewis rats, but not in resistant F344 or nude Lewis rats. Because continuous exacerbations may be one possible mechanism underlying chronic disease, we studied the mechanism of these flare-up reactions in Lewis and F344 rats. Injection of SCW into the right knee joint of rats induced a transient monoarthritis in both strains. Reactivation of the subsided arthritis by i.v. administration of the same antigen could be evoked only in the Lewis rat. Even repeated i.v. challenges with SCW failed to induce a flare-up reaction in the F344 rat, while the Lewis rat went through an exacerbation after every challenge. Removal of T lymphocytes by monoclonal antibodies before induction of an exacerbation rendered Lewis rats refractory to flare-up reactions, thus indicating the T cell-dependence of this reaction. Furthermore, when cell walls from heterologous bacteria were tested for their capacity to induce exacerbations of SCW-induced monoarthritis and to induce proliferation of SCW-specific T lymphocytes in vitro, a strong correlation between both features was found, again pointing to a role for SCW-specific T cells in exacerbations. Together, these data support our hypothesis that chronic arthritis is the result from repeated reactivations of a waning arthritis which are dependent on antigen-specific T lymphocytes.